(untitled) - Levi, Maurice D. (New York, 2009)
The fifth edition of Maurice D. Levi’s classic textbook has been updated to incorporate the massive changes in the world of international finance of the past few years. In particular, the emergence of new markets is given broad coverage – particularly the rise to financial prominence of China and India and other growth economies in Asia and elsewhere. Key features of the book include: the impact of globalization and the greater connectedness of national economies and the world economy as a whole. probably the best introduction to exchange rates available and how they directly impact upon firms as well as governments.
Tài chính quốc tế
Keywords: International finance,International business enterprises; Finance